Group analysis of two-dimensional Schrödinger equations with variable mass - Zasadko, T.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
The first-order integrals of motion for Schrödinger equations with variable mass are classified. Eight classes of such equations with non-equivalent symmetries are specified. They include integrable, superintegrable, and maximally superintegrable systems. A complete set of solutions for one of these systems is presented explicitly.